PENERAPAN MODEL GALUR DENGAN AKTIVITAS KONTEKSTUAL UNTUK MENINGKATKAN LITERASI EKONOMI DASAR PADA PEMBELAJARAN TEMATIK KELAS III SD PLUS IT PADANGSIDIMPUAN - Nahdah Faizah Harahap; Khoirul Bariah Rambe; Rama Nida Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research aims to improve the basic economic literacy of third-grade students at SD PLUS IT Padangsidimpuan through the application of the GALUR learning model integrated with contextual learning activities. The study involved 23 students and was carried out in two cycles following the Kemmis and McTaggart framework of planning, action, observation, and reflection. Data were collected through observations, interviews, learning outcome tests, and documentation. The implementation of contextual activities—such as canteen observation and a mini-market simulation—enabled students to experience authentic economic situations, thereby strengthening their understanding of needs and wants, goods and services, and simple transaction processes. The findings indicate a significant improvement in learning outcomes, with the average score increasing from 55 in the pre-cycle to 69 in Cycle I and 84 in Cycle II, along with an increase in mastery from 61% to 91%. These results demonstrate that the integration of the GALUR model and contextual activities effectively enhances students’ economic literacy and supports more meaningful thematic learning in elementary education